Island Encounters Timor-Leste from the outside in - Palmer, Lisa (Monographs in Anthropology, 2021)
Island Encounters is a narrative of Timor shaped by a journey from the outside in. Incorporating the author's experiences from more than two decades of involvement with Timor-Leste and, more particularly, the months she spent travelling with her family from west to east in 2018, Palmer traces paths redolent in longing and learning, belonging and bewilderment, courage and conviction to tell of an island divided by colonialism and conflict. The book's themes shuttle back and forth across the island, weaving together the past, present and future in deeply felt histories and personal stories that create the shared fabric of Timorese people's lives. Offering a counterpoint to modernising development narratives, Island Encounters tells of people's quiet determination to maintain their relationships between their lands, waters, traditions and each other. By foregrounding the ways in which ancestral pathways and cultural politics inform and course through everyday life on island Timor, Palmer reveals the richness of the rituals and customary practices that underpin Timorese lives and the lives of those entwined with them. And, all along the way, Island Encounters shows how Timor and its diverse peoples are working with, and re-working, confounding and being confounded by, the ever-desirous heart of development.